PENDIDIKAN AGAMA ISLAM (PAI) PADA ANAK USIA DINI DI RAUDHATUL ATHFAL (RA) DARUL HUDA MATARAM BARU LAMPUNG TIMUR - daman, Damanhuri; Jamiluddin Yacub; Nur Indahsari; Ermanita Permatasari (AZZAHRA, 2021)
PAI learning in early childhood still shows various problems that are less encouraging. The learning process of Islamic Education is only limited to the process of transfer of knowledge of Islamic Religion so that it is less able to convert it into "meaning" and "value". PAI puts more emphasis on the knowing and doing aspects and has not yet addressed the aspects of being. The failure to organize PAI so far is due to malpractice in education only paying attention to cognitive aspects and neglecting the development of affective aspects. To be able to overcome and solve these problems, a PAI learning process is needed that is in accordance with the needs of students. This study uses a qualitative descriptive approach, interview data collection techniques, observation and documentation. The results of this study indicate that the implementation of Islamic religious education in RA is carried out by teaching morals to children, praying fardhu properly and correctly, training children to learn Alquran with Iqro. Inhibiting factors in implementing early childhood religious education there is no awareness and understanding from each child's parent to guide children in carrying out religious teachings, such as praying five times a day, learning to read the Koran and doing good to others and the influence interaction in the surrounding community. Efforts to overcome obstacles in implementing early childhood religious education are to provide exemplary and attention and affection for children, so that they can follow what parents and teachers instruct